EFEK ANTIINFLAMASI EKSTRAK DAUN SEMBUKAN (Paederia scandens) PADA TIKUS WISTAR - Evy Tri Utami; Rebecca Azary Kuncoro; Islamy Rahma Hutami; Finsa Tisna Sari; Juni Handajani (Faculty of Pharmacy, Universitas Gadjah Mada, 2011)
Inflammation is a protective action that role on defending mechanism to defeat agent causing cell injury. Glucoside of skunkvine (Paederia scandens) has anti-inflammation effect. The aim of this study was to know the anti anti-inflammatory effect of skunkvine (Paederia scandens) extract on artificial edema in Wistar rat. Thirty-five Wistar rats were divided into 7 groups, each group consisted 5 rats. In the control and treatment groups, aquadest (negative control), fenilbutazon (positive control), skunkvine extracts in dose 10mg/kgBW, 20mg/kgBW 30mg/kgBW, 40mg/kgBW, and 50mg/kgBW were administered per orally. In order to induce the edema, one hour after administration, in each group, right hind paw of the rats was injected subcutaneously with by 1% carrageenin. The volume measurement performed with one hour interval for 5 hours assessing with pletysmometer. The data were analyzed by ANOVA. The result of this study showed there was significant difference on group with skunkvine extract 20mg/kg BW to negative control and positive control. In conclusion, that the skunkvine extract 20 mg/kgBW has potency as anti-inflammation substance.